Radio Frequency Identification and Near Field Communication Door Lock Using Arduino for Bloomridge Integrated School: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study aims to create a radio-frequency identification and near-field communication doorlock. To be able to provide access to the students, professors, staff, and other individuals. Thisis convenient right now and in the future. Over traditional lock and key access in schools,keyless access locks have a number of benefits. Electronic door locks with RFID capabilitiesoffer convenience and improved security to clients. RFID key cards offer security againstunauthorized users because they are significantly more difficult to replicate than keys. RFIDtechnology not only offers a great level of protection, but it is also incredibly user-friendly. Theresearchers designed the Radio Frequency Identification and Near Field CommunicationDoor Lock for Bloomridge Integrated School to have a more secure lock.The proponents have found a solution for the client's problem with the help of radio frequencyidentification and a near-field communication door lock for their school. They are delightedthat the researcher developed a more secure lock for their facility for the safety of the faculty,employees, and students.Radio-frequency Identification Technology communicates between two devices, tags, andreaders, using electromagnetic fields. Radio-frequency identification door locks operate byestablishing a connection between credentials and the reader via radio waves. Access controlproviders have discovered the wireless capabilities and flexibility of RFID technology to bevaluable, going beyond the standard lock and key.
Keywords: IT & Management